A comparison of treatment outcomes among HIV positive tuberculosis patients receiving DOTS and fixed dose combination in Visakhapatnam - Kuppli, Sai Sushma; Bhimarasetty, Devi Madhavi; Lotheti, Siva Kumar (International Journal Of Community Medicine And Public Health, 2019)
Background: Tuberculosis is a communicable disease which requires special attention in HIV patients. According to newer guidelines, the treatment regimen for tuberculosis has been changed from intermittent DOTS to daily FDC. This study was taken up to explore effectiveness of fixed dose combination in comparison to intermittent DOTS. Objective was to compare the treatment outcomes for tuberculosis among HIV positive TB patients receiving intermittent DOTS with those receiving daily fixed dose combination (FDC). Methods: A retrospective cohort study was done during November 2017. The data was collected from patient records in an ART centre, attached to King George Hospital, Visakhapatnam. All the HIV patients newly registered for anti-tubercular treatment at the ART center, during 1st quarter of 2016(intermittent DOTS) were compared with those registered during 1st quarter of 2017(FDC). The treatment outcomes include (1) treatment success (completed/ cured), and (2) other treatment outcomes (lost to follow up (LFU), Death). Data was analysed using MS Excel. Association of factors affecting treatment outcomes was tested using chi-square test. Results: Out of a total 83 patients, 34 were on intermittent DOTS and 49 on FDC. The percentage of treatment success in intermittent DOTS was higher than FDC (p=0.06, chi-square value=3.42). The percentage of deaths in FDC is high when compared to intermittent DOTS (P=0.74, chi-square=3.1762). In subject receiving FDC, it was observed that more females had treatment success as compared to males (p=0.28, chi square=1.13). Conclusions: There is no statistically significant difference in the TB treatment outcomes of intermittent DOTS and FDC.